Elucidation of the inhibitory effect of (+)-hopeaphenol on polyinosinic-polycytidylic acid-induced innate immunity activation in human cerebral microvascular endothelial cells - Liu Xu; Zaiqiang Yu; Yoshinori Uekusa; Shogo Kawaguchi; Haruhisa Kikuchi; Kazuyuki Daitoku; Masahito Minakawa; Shigeru Motomura; Ken-Ichi Furukawa; Yoshiteru Oshima; Kazuhiko Seya; Tadaatsu Imaizumi (Elsevier, 2022)
Drug development for regulating the innate immune system is important for the prevention and treatment of autoinflammatory and autoimmune diseases. In this context, we investigated the effect of resveratrol derivatives on the inflammatory reactions in the brain. Resveratrol, which can be found in Vitis plants in the form of oligomers, exhibits neuroprotective effects; however, its regulatory effects on innate immunity are still unclear. We examined the effects of (+)-hopeaphenol, a resveratrol tetramer, and its derivatives on the polyinosinic-polycytidylic acid (poly IC)-induced production of interferon (IFN)-β and C-X-C motif chemokine 10 (CXCL10) in the cultured human cerebral microvascular endothelial cell line hCMEC/D3. (+)-Hopeaphenol (1-10 μM) inhibited the poly IC-induced production of not only CXCL10 but also retinoic acid-inducible gene-I in a dose-dependent manner and significantly reduced the poly IC-induced IFN-β gene expression and protein release from hCMEC/D3 cells by inhibiting the phosphorylation of p65 but not that of the interferon regulatory transcription factor IRF3. A docking study indicated a high affinity of (+)-hopeaphenol for p65. These results suggest that (+)-hopeaphenol can regulate the innate immune system by inhibiting the poly IC/IFN-β/CXCL10 signaling axis via suppression of the phosphorylation of the transcription factor NF-ĸB.